Glycopolymer and Poly(β-amino ester)-Based Amphiphilic Block Copolymer as a Drug Carrier - Sahkulubey Kahveci, Elif L.; Kahveci, Muhammet U.; Celebi, Asuman; Avsar, Timucin; Derman, Serap (American Chemical Society (ACS), 2022)
Glycopolymers are synthetic macromolecules having pendant sugar moieties and widely utilized to target cancer cells. They are usually considered as a hydrophilic segment of amphiphilic block copolymers to fabricate micelles as drug carriers. A novel amphiphilic block copolymer, namely, poly(2-deoxy-2-methacrylamido-d-glucose-co-2-hydroxyethyl methacrylate)-b-poly(β-amino ester) [P(MAG-co-HEMA)-b-PBAE], with active cancer cell targeting potential and pH responsivity was prepared. Tetrazine end functional P(MAG-co-HEMA) and norbornene end functional PBAE blocks were separately synthesized through reversible addition fragmentation chain transfer polymerization and Michael addition-based poly-condensation, respectively, and followed by end-group transformation. Then, inverse electron demand Diels Alder reaction between the tetrazine and the norbornene groups was performed by simply mixing to obtain the amphiphilic block copolymer. After characterization of the block copolymer in terms of chemical structure, pH responsivity, and drug loading/releasing, pH-responsive micelles were obtained with or without doxorubicin (DOX), a model anticancer drug. The micelles exhibited a sharp protonated/deprotonated transition on tertiary amine groups around pH 6.75 and the pH-specific release of DOX below this value. Eventually, the drug delivery potential was evaluated by cytotoxicity assays on both the noncancerous human umbilical vein endothelial cell (HUVEC) cell line and glioblastoma cell line, U87-MG. While the DOX-loaded polymeric micelles were not toxic in noncancerous HUVEC cells, being toxic only to the cancer cells indicates that it is a potential specific cell targeting strategy in the treatment of cancer.
Keywords: Drug Carriers; Doxorubicin; Humans; Esters; Hydrogen-Ion Concentration; Norbornanes; Micelles; Polyethylene Glycols